ENT 530 Social Media Portfolio: Mary Kay / Nuramanina Hishamudin - Hishamudin, Nuramanina (2020)
This portfolio is about the type of posting in the social media and the platform uses to promote the business. There are basically three type of copywriting which are hard sell, soft sell and teaser. The seller who just start the business can use social media as platform to promote the product or services. For example, FB Page, Instagram business and Whatsapp business. This is because those platforms they have the algorithm and the strategy to get highest level of viewers. From here people will start to notice the product that the seller promote. There is total 7 teaser, 16 hard sell and 16 soft sells. This is because for the target customer to notice the product or service that are promote, the seller needs to consistence in posting. For each type of copywriting, there is a formula and key word to attract the target customer’s attention. The product use for this task is skincare, makeup, and body care products. The target customers for the product are wide and almost for everyone that is 18 years old and above. This is because everyone has skin and people nowadays are very concern about their skin especially face. Other that that the products have wide range and specific for every skin type and skin issue. For example, people at the age of 20’s focus for anti-aging issue and people at the age of 50’s focus for repairing skin issue. The product is Mary Kay.